The Role of Barbed Sutures in Wound Closure Following Knee and Hip Arthroplasty: A Review - Faour, Mhamad; Khlopas, Anton; Elmallah, Randa K.; Chughtai, Morad; Kolisek, Frank R.; Barrington, John W.; Mont, Michael A. (The Journal of Knee Surgery, 2018)
Lower extremity joint arthroplasty procedures often require a large incision to have an adequate exposure, which subsequently leads to lengthy wounds that may contribute to long closure, anesthesia, and overall operative times. The recently introduced knotless barbed suture may provide better outcomes, faster closure time, and decreased material utilization. Therefore, the aim of this study was to review the impact of barbed sutures on: (1) wound-related complications; (2) closure and operative time; (3) patient outcomes (range of motion and Knee Society Scores [KSS]); and (4) effects on cosmesis and patients' satisfaction. A literature search was performed using up to February 2017. Barbed sutures were associated with shorter closure times, shorter operative times, and larger cost savings per procedure as well as comparable wound complication rates after total joint arthroplasty. Although the current review is limited by the number of studies included, it demonstrates that overall, barbed sutures contribute to surgical efficiency when compared with conventional skin closure modalities.
Keywords: barbed suture; wound closure; arthroplasty; outcomes; complications